De novo tanscriptome sequencing and functional annotation of differentially expressed genes in large and small seeds of common cocklebur (Xanthium strumarium L.) during seed development - Iman Nemati; Mohammad Sedghi; Ghasem Hoseini Salekdeh; Reza Tavakkol afshari; Mohammadreza Naghavi (علوم و فناوری بذر ایران)
Common cocklebur (Xanthium strumarium L.) is a widespread weed with high medical value and interested for researchers because of deep dormancy in one of its two seeds in one bur. However, lack of genomic data has led to low information about it. Transcriptome large and small seeds were sequenced using Illumina platform to identify and functional analysis of differentially expressed transcripts in two seeds. Identified sequences in each seeds were compared and differentially expressed genes were functionally annotated. In this research 191192 sequence with a mean of 989.69 bp were detected. Sequence similarity analysis and functional analysis was carried out aginst nr, GO and KEGG databases. Differentially expressed genes had the most similarity with sunflower (83.41 per cent) in terms of top hits. GO analysis led to identify 615 functional annotation distributed in 36 categories. The most abomdant GO in biological process was biosynthesis. Results of our research shows the higher biosynthetic and metabolic processes in large seed of certain bur rather than the small one and also key regulatory role of transcription during seed development.